Households’ Borrowing Intentions During the COVID-19 Crisis: The Role of Financial Literacy - Łukasz Kurowski (Journal of Banking and Financial Economics)
This study aims to determine the role of financial literacy in households’ borrowing intentions during the coronavirus pandemic. Employing a survey of 1,300 Polish citizens conducted during the COVID-19 crisis and an instrumental variable analysis, we found that financial literacy significantly increases households’ borrowing intentions. This applies to financially sound consumers both in crisis and normal times. In terms of sociodemographic features, young adults and the less educated are less willing to borrow during the pandemic.